Application of PPP solution to determine the absolute vertical crustal movements: case study for Northeastern Europe - Kowalczyk, Kamil; Bogusz, Janusz (International Conference “Environmental Engineering”, 2017)
To estimate the relationship between vertical movements of the Earth’s crust, geoid temporal changes and Mean Sea Level (MSL) variations, a knowledge about the absolute (determined from satellite and space techniques) height changes over time is required. In this paper, we give an idea of determining the height changes with a use of Vertical Switching Edge Detection (VSED) algorithm. On the basis of the least squares estimation, the VSED method detects the discontinuities in time series and determines the values of jumps at the same time. We used the time series from PPP (Precise Point Positioning) solution obtained in NGL (Nevada Geodetic Laboratory) using satellite data gathered at more than 50 permanent stations located in Latvia, Lithuania and northeastern Poland. The minimum time span of data was set up to 3 years. Data were pre-analyzed by removing outliers and interpolating small gaps. The obtained results give an overview of a possibility of the proposed method to be used and the ongoing vertical movements on the area we considered.